Frumarová, Kateřina, Tomáš Grygar, Zdeněk Koudelka, Lukáš Potěšil, Olga Pouperová, Radovan Suchánek and Martin Škurek: Administrative Justice. Praha: Leges, 2022. 671 p. ISBN 978-80-7502-611-8 - Tomáš Čičmanec (Societas et Iurisprudentia, 2023)
Reviewing the scientific monograph Frumarová, Kateřina, Tomáš Grygar, Zdeněk Koudelka, Lukáš Potěšil, Olga Pouperová, Radovan Suchánek and Martin Škurek: Administrative Justice.